Mechanosensitive afferent units in the hypogastric nerve of the cat. - Floyd, K (1976)
1. Recordings have been made from ninety single afferent units in the hypogastric and lumbar splanchnic nerves of the cat. 2. The majority of units examined had properties similar to those previously described in the splanchnic nerve: they were slowly adapting mechanoreceptors with one to six punctate mechanosensitive sites distributed mainly along blood vessels as they approached the viscera in peritoneal ligaments; they had a wide range of mechanical thresholds and conduction velocities in the range 0.5-24 m s-1. 3. Receptive fields were found over the bladder base or its peritoneal ligaments or both, on the uterus or broad ligament or both, on the colon or mesocolon or both, and in association with the ureter, vas deferens, prostate or pelvic fat pads. 4. Discharges from afferent units associated with the bladder were investigated during spontaneous (or reflex) bladder contractions, passive distensions, and tetanic contractions induced by electrical stimulation of the sacral spinal cord. The mean spike rates of the adapted (tonic) discharges, observed during distensions and induced tetani, differed over part of the range of intravesical pressures examined. Their behaviour is discussed in relation to the concept of 'in series' tension receptors within the bladder wall.